Pegasus - McKinley, Robin (New York G.P. Putnam's Sons, 2010)
Because of a thousand-year-old alliance between humans and pegasi, Princess Sylvi is ceremonially bound to Ebon, her own pegasus, on her twelfth birthday, but the closeness of their bond becomes a threat to the status quo and possibly to the safety of their two nations.
1070L
Keywords: Pegasus (Greek mythology) -- Juvenile literature; Human-animal communication; Princesses; Magic; Fantasy; Fantasy fiction